Tax evasion: Criminological characteristic, problems of criminal liability application and improvement of the mechanism of crime suppression - Karzhassova, G.B. (Middle-East Journal of Scientific Research 16 (7), 907-912, 2013)
The paper investigates tax evasion in the Republic of Kazakhstan as a crime in terms of the science of criminology and criminal law. This type of crime causes a very significant harm to the state budget of Kazakhstan and currently has a strong tendency to further growth, so the issues of research of tax crime and one of its most dangerous manifestations, namely tax evasion, are important. The author considers different points of view on the determinants of tax crime, beginning with a look at the macro-level factors, goes to the micro-level factors and concludes about further necessity of criminalization of a number of actions that are used to avoid tax payment. The author argues for the low efficiency of decriminalization of tax evasion by increasing the statutory amount of major damage and demonstrates the usefulness of a comprehensive taxamnesty as an alternative to decriminalization. Having performed a comparative analysis of the rules of criminal liability for tax evasion, the author notes that in various modern legal systems the graduation of the degree of responsibility for tax evasion is based on determining the size of the concealed amounts. The author comes to a conclusion about the need of complex improvement of the rules of various branches of legislation to effectively combat tax crimes.
Keywords: Criminalization; Tax amnesty; Tax crime; Tax evasion; Taxes